2016
DOI: 10.1016/j.stem.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Dual SMAD Signaling Inhibition Enables Long-Term Expansion of Diverse Epithelial Basal Cells

Abstract: SUMMARY Functional modeling of many adult epithelia is limited by the difficulty of maintaining relevant stem cell populations in culture. Here, we show that dual inhibition of SMAD signaling pathways enables robust expansion of primary epithelial basal cell populations. We found that TGFβ/BMP/SMAD pathway signaling is strongly activated in luminal and suprabasal cells of several epithelia, but suppressed in p63+ basal cells. In airway epithelium, SMAD signaling promotes differentiation, and its inhibition lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
334
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(348 citation statements)
references
References 42 publications
14
334
0
Order By: Relevance
“…3A). With the BMP inhibitors dorsomorphin and DMH1, no change in the proportion of ciliated and secretory cells was seen, although other studies have suggested that inhibition of BMP signaling inhibits basal cell differentiation (Mou et al, 2016;Tadokoro et al, 2016). Addition of BMP4 ligand results in small spheres with mostly basal cells and few Krt8 + cells (Fig.…”
Section: Facs or Macsmentioning
confidence: 88%
See 1 more Smart Citation
“…3A). With the BMP inhibitors dorsomorphin and DMH1, no change in the proportion of ciliated and secretory cells was seen, although other studies have suggested that inhibition of BMP signaling inhibits basal cell differentiation (Mou et al, 2016;Tadokoro et al, 2016). Addition of BMP4 ligand results in small spheres with mostly basal cells and few Krt8 + cells (Fig.…”
Section: Facs or Macsmentioning
confidence: 88%
“…Various methods have been developed for isolating and growing these basal cells from different regions of the normal human respiratory system, including nasal epithelium, ʻlarge airways', which include the trachea, primary bronchi and intralobar bronchi down to about the third or fourth generation, and from bronchial brushings (Hackett et al, 2011;Randell et al, 2011). The most efficient methods for expanding and cloning TRP63 + KRT5 + human basal cells involves culturing them either on irradiated mouse 3T3-J2 fibroblasts in the presence of the Rho kinase inhibitor Y-27632 (Butler et al, 2016;Kumar et al, 2011;Suprynowicz et al, 2012), or with a Rho kinase inhibitor together with inhibitors of Smaddependent signaling through the BMP and TGFβ pathways and an activator of Wnt signaling (Mou et al, 2016). The progenitor properties and differentiation capacity of these basal cells can then be followed in organoid cultures.…”
Section: Basal Progenitor Cellsmentioning
confidence: 99%
“…Nevertheless, expansion of donorderived cell supplies for preclinical studies of CFTR modulators will be enhanced by the CRC method. Recently, inhibition of SMAD signaling pathways in a feeder-free culture system was used to expand airway basal stem cells (17). However, decreases in CFTR rescue as a function of cell expansion were quite profound in ALI cultures generated with this method.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Human esophagus can be cultured on an air-liquid interface or on the matrix of decellularized esophageal tissue. [100,101] Yet, these cultures lack the supporting tissue around the esophagus along with a tubular structure that an esophageal organoid could incorporate. The proper matrix and Biomaterials for 3D Cell Biology Prospective Article media composition will need to be determined in order to generate esophageal organoids from primary tissue and hPSCs.…”
Section: Esophageal Organoidsmentioning
confidence: 99%